2021
DOI: 10.1002/fsh.10669
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Experimental Validation of Two Different Predation Sensors for Instrumenting Acoustic Transmitters in Fisheries Research

Abstract: We validated the performance of two types of predation sensors on acoustic telemetry transmitters in a combined field and laboratory study design using juvenile Atlantic Salmon Salmo salar and a predator large Brown Trout Salmo trutta. One tag model was outfitted with an acid‐sensitive predation sensor, and the other was equipped with a tilt‐based orientation sensor. We found similar response times for the two tag types to identify a predation event (time between known ingestion of a tagged fish and triggering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…In our study, six of the twelve smolts that died, died without the predation sensor indicating predation. This might be due to mortality caused by surgery, tag burden, or natural mortality, but during a parallel laboratory validation study of the sensor, a false‐negative rate of 50% was observed (Lennox et al 2021), corresponding to the 50% unknown mortalities in our field study. False positives (i.e.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In our study, six of the twelve smolts that died, died without the predation sensor indicating predation. This might be due to mortality caused by surgery, tag burden, or natural mortality, but during a parallel laboratory validation study of the sensor, a false‐negative rate of 50% was observed (Lennox et al 2021), corresponding to the 50% unknown mortalities in our field study. False positives (i.e.…”
Section: Discussionmentioning
confidence: 77%
“…Accounting for possible alternative causes of mortality will be important, although identifying avian predation requires further tag validation (i.e. for aquatic birds such as ducks and cormorants) and may be impossible for fully terrestrial species such as raptors and corvids (Lennox et al, 2021). Factors such as water temperature, conspecific density, predator density, and water flow will affect smolt migration patterns (Thorstad, Whoriskey, et al, 2012), contributing to interannual variation in survival that must be accounted for in a multi‐year study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider the specification of an actual acoustic tag manufactured by Thelma-Biotel Inc., Trondheim, Norway [10]. These acoustic tags are used globally in applications to monitor fauna in marine environments and to track migration patterns [35], [36]. The mobile node is an acoustic tag (model: ID-HP16) emitting 69kHz single-tone signals of intensity 158dB re 1µPa @ 1m.…”
Section: F Numerical Investigation Setupmentioning
confidence: 99%